Time course of pulmonary burden in mice exposed to residual oil fly ash - Carvalho, Giovanna Marcella Cavalcante; Nagato, Lilian Katiê da Silva; Fagundes, Sheila da Silva; dos Santos, Flávia Brandão; Calheiros, Andrea Surrage; Malm, Olaf; Bozza, Patricia Torres; Saldiva, Paulo Hilário N.; Faffe, Débora Souza; Rocco, Patricia Rieken Macedo; Zin, Walter Araujo (Frontiers in Physiology, 2014)
Residual oil fly ash (ROFA) is a common pollutant in areas where oil is burned. This particulate matter with a broad distribution of particle diameters can be inhaled by human beings and putatively damage their respiratory system. Although some studies deal with cultured cells, animals, and even epidemiological issues, so far a comprehensive analysis of respiratory outcomes as a function of the time elapsed after exposure to a low dose of ROFA is wanted. Thus, we aimed to investigate the time course of mechanical, histological, and inflammatory lung changes, as well as neutrophils in the blood, in mice exposed to ROFA until 5 days after exposure. BALB/c mice (25±5 g) were randomly divided into 7 groups and intranasally instilled with either 10 µL of sterile saline solution (0.9% NaCl, CTRL) or ROFA (0.2 µg in 10 L of saline solution). Pulmonary mechanics, histology (normal and collapsed alveoli, mononuclear and polymorphonuclear cells, and ultrastructure), neutrophils (in blood and bronchoalveolar lavage fluid) were determined at 6 h in CTRL and at 6, 24, 48, 72, 96 and 120 h after ROFA exposure. ROFA contained metal elements, especially iron, polycyclic aromatic hydrocarbons, and organochlorines. Lung resistive pressure augmented early (6 h) in the course of lung injury and other mechanical, histological and inflammatory parameters increased at 24 h, returning to control values at 120 h. Blood neutrophilia was present only at 24 and 48 h after exposure. Swelling of endothelial cells with adherent neutrophils was detected after ROFA instillation. No neutrophils were present in the lavage fluid. In conclusion, the exposure to ROFA, even in low doses, induced early changes in pulmonary mechanics, lung histology and accumulation of neutrophils in blood of mice that lasted for four days and disappeared spontaneously.